The history of granulite-facies metamorphism and crustal growth from single zircon U-Pb geochronology: Namaqualand, South Africa - Robb, L; Armstrong, R; Waters, D (1999)
The Namaqualand Metamorphic Complex is a well-exposed, Mesoproterozoic, low-pressure, amphibolite-granulite-facies terrane flanking the Archaean Kaapvaal Craton of southern Africa. Previous isotopic dating in the region suggests an ~150 my period of prograde granulite-facies metamorphism and episodic granite emplacement in the mid-crust. In contrast, thermal modelling suggests that sub- and superjacent magmatic accretion should not have exceeded 30 my in duration. This enigma is resolved by precise U-Pb zircon SHRIMP dating of the major orthogneissic units of the region. These data point to Kibaran crustal growth at 1220-1170 Ma, which occurred on the margins of a Palaeoproterozoic (2000-1800 Ma) continental nucleus. A later, distinct, orogenic episode, here termed the Namaquan (time equivalent of the Grenvillian), involved crustal thickening and magmatism at 1060-1030 Ma and was responsible for, and coeval with, the peak of metamorphism. Low-P granulite-facies metamorphism resulted from advective heating and crustal thickening by magmatic accretion over a 30 my interval.